Integrated design of GaN-on-Si power devices and drivers - Yan Zhangzhe; Zhou Jianjun; Kong Yuechan (Dianzi Jishu Yingyong)
An all-GaN power chip is designed to meet the application requirements of high-frequency power modules. The chip integrates the driver circuit and 300 V power devices, which effectively reduces the parasitic inductance caused by the discrete package, and the integrated design can improve the chip's noise immunity and reliability. The chip is prepared in GaN-on-Si process platform and adopts E/D mode IC design. The driver circuit of the chip has an output signal rise time of 4.3 ns and a fall time of 3.4 ns at a switching frequency of 2 MHz, and the power devices are able to work stably at 300 V.